Influence of the Treaty of Lisbon on Poland’s strength in the Council of the European Union (Economic and Political Thought, 2015)
Changes introduced by the Treaty of Lisbon resulted in a substantialshift of vote strength between the member states of the Council of theEuropean Union. It also had great influence on the position of Poland andits bargaining power in this institution. Although the Treaty modified onlythe formal determinants of strength, it changed the dynamics of the decisionmakingprocess as well as the importance of the European Commission,the European Parliament and the Council of the European Union in thisprocess. The article highlights the new way of weighing votes in the Councilof the EU, the increase in the scope of decisions taken by qualified majorityand the introduction of new competences clauses, which had impact on theposition of Poland in this institution. It shows a substantive shift of votestrength towards the four biggest member states at the expense of countrieswith smaller population. As a result, it will be more difficult for Poland tobuild its bargaining power based on formal-legal factors. Thus, the skills inmulti-level and parallel negotiations, presenting own interests, reliable andconsistent arguments, and promotion of common initiatives will become moreimportant. The work makes a wide use of multiplayer voting games, especiallymathematical indexes of strength in order to demonstrate its flow between themembers of the Council of the EU. The author also uses a formal-dogmaticmethod in order to analyse the contents of the source materials, includingmainly the primary legal acts. The mathematical indexes of strength, for theneeds of the analysis presented in the article, were calculated with the use ofthe program POWERGEN 1.0.